PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA DEALER HONDA RAJA JAYA MOTOR MAUMERE - Kristofurus Glenaldi Laju; Antonius Phillipus K.Gheta; Dimas Realino (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2026)
This research aimed to determine the influence of facilities and service quality on guest satisfaction at Mathilda Hotel Maumere. The background of this research was from the increasing competition in the hotel industry in Sikka Regency, as well as initial findings indicating a discrepancy between guests' expectations and the actual services received, particularly in terms of limited facilities and inconsistencies in service quality. This research used a quantitative method with an associative research design. The sample consisted of 87 respondents selected through purposive sampling from a population of 725 hotel guests. Data were collected using a questionnaire instrument and analyzed through instrument testing, classical assumption tests, and multiple linear regression analysis. The results of the research showed that: (1) facilities had a positive and significant effect on guest satisfaction, meaning that the better the facilities provided, the higher the level of guest satisfaction; (2) service quality also had a positive and significant effect on guest satisfaction, indicating that fast, friendly, and professional service could improve the guest stay experience; and (3) facilities and service quality simultaneously had a significant effect on guest satisfaction at Mathilda Hotel Maumere. These findings emphasized that efforts to improve physical comfort and the quality of service interactions were essential in increasing guest satisfaction and loyalty.